KOMISI PENGAWAS PERSAINGAN USAHA DALAM PENEGAKAN HUKUM PERSAINGAN USAHA - Alum Petronella Simbolon (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2008)
Act Number 5 of 1999 concerning Prohibition of Monopoly Practices and Unfair Competition has enacted in 2000. To supervise the enactment of the Act, the Commission of Business Competition (KPPU) was established. KPPU is an independent institution. The member of KPPU are appointed by President with approval of legislature. In performing its duties, KPPU is responsible to President. The Legal Status of the institution in performing both its duties and authority was clearly regulated in Article 35 and 36 of the Act. According to the Article 35 of the Act, the duties of the institution include performing the valuation of agreement resulting in monopoly practices and of whether or not there is dominant position abuse; providing government with recommendation and consideration in policies related to the monopoly practices and the unfair business competition; conducing investigation and/or inspection on the presumptive case of monopoly practices; inspecting the related proof instrument; deciding and stipulating whether or not there loss in one of the related business subject; informing the commission’s stipulation to the business subject that violated the stipulation of the Act.